(untitled) (Revista de Ciências Agroveterinárias, 2002)
This study evaluated in vitro production of sclerotia of Sclerotium rolfsii and Sclerotinia sclerotiorum in different culture media, temperatures, and light conditions. This kind of standardization is necessary for the production of pure inoculum, that could be used for tests of pathogenicity and plant resistance to diseases. These experiments were conducted under standard laboratory conditions in a completely randomized experimental design. The results of the trials showed that S. rolfsii produced more sclerotia on PDA (potato-dextrose-agar) at 27ºC under 24 h of fluorescent white-light. However, S. sclerotiorum produced more sclerotia on PDA at 21ºC independent of light condition (light or darkness). PEGA (peptona, yeast extract, glucose, agar), NA (nutrient agar), and FA (potato starch, dextrose, agar) media did not induce any production of a significant amount of sclerotia.